Extreme Metal Music and Anger Processing - Sharman, Leah; Dingle, Genevieve A. (Frontiers in Human Neuroscience, 2015)
The claim that listening to extreme music causes anger and expressions of anger such as aggression and delinquency has yet to be substantiated using controlled experimental methods. In this study, 39 extreme music listeners aged 18 to 34 years were subjected to an anger induction, followed by random assignment to 10 minutes of listening to extreme music from their own playlist, or 10 minutes of silence (control). Measures of emotion included heart rate and subjective ratings on the Positive and Negative Affect Scale (PANAS). Results showed that ratings of PANAS hostility, irritability, and stress increased during the anger induction, and decreased after the music or silence. Heart rate increased during the anger induction and was sustained (not increased) in the music condition, and decreased in the silence condition. PANAS active and inspired ratings increased during music listening, an effect that was not seen in controls. The findings indicate that extreme music did not make angry participants angrier rather it appeared to match their physiological arousal and result in an increase in positive emotions. Listening to extreme music may represent a healthy way of processing anger for these listeners.